(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The Sensitivity towards animal welfare, although it is now well rooted in the collective consciousness, does not seem to have found yet full recognition by the legislator. The paper, taking its cue from the recent amendment of the art. 9 of the Constitutional Charter which entrusts to the law of the State “the regulation of the ways and forms of protection of animals”, tries to reason on the possible configurability of an animal subjectivity, verifying whether this element can be already considered acquired in the light of living law, or instead if it represents a foreseeable outcome of the legislative processes still in progress.